1993
DOI: 10.1007/bf00315285
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear kinetics of threo-methylphenidate enantiomers in a patient with narcolepsy and in healthy volunteers

Abstract: We have studied the pharmacokinetics of methylphenidate enantiomers after the oral administration of different doses of racemic methylphenidate to one patient with narcolepsy and to four healthy volunteers. The plasma concentrations of (+)-methylphenidate were much higher than those of (-)-methylphenidate after each dose in all subjects. In the patient the oral clearance (CL/f) of (+)-methylphenidate fell 3-fold and the area under the concentration-time curve (AUC) rose 7-fold when the dose was increased from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
24
0

Year Published

1995
1995
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 13 publications
7
24
0
Order By: Relevance
“…The in vivo regional distribution in rat brain of the positive and negative enantiomers of DL-threomethylphenidate was investigated by Aoyama et al (1994a). Results obtained on administration of the individual enantiomers were similar to those obtained after administration of the racemate.…”
Section: Binding Of Methylphenidate To Dopamine Transporterssupporting
confidence: 54%
See 1 more Smart Citation
“…The in vivo regional distribution in rat brain of the positive and negative enantiomers of DL-threomethylphenidate was investigated by Aoyama et al (1994a). Results obtained on administration of the individual enantiomers were similar to those obtained after administration of the racemate.…”
Section: Binding Of Methylphenidate To Dopamine Transporterssupporting
confidence: 54%
“…They also found some evidence that there may be dose dependency associated with the metabolism of racemicmethylphenidate. Aoyama et al (1993) reported that the positive enantiomer of methylphenidate showed dose-dependent kinetics in humans, probably because of saturation of the presystemic elimination of the drug.…”
Section: Pharmacokineticsmentioning
confidence: 98%
“…25 The ratio of d-MPH to l-MPH reported in other studies has varied considerably (5-to 230-fold). 16,25 In this study, the ratio of d-MPH to l-MPH for NWP06 and IR MPH easily falls within the range reported in the literature.…”
Section: Discussionsupporting
confidence: 75%
“…This finding is consistent with that of extensive enantiospecific pharmacokinetic studies that have measured both isomers and found the l-isomer to generally attain only a small fraction of that of circulating concentrations of d-MPH (Table 1). [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] In addition, the plasma half-life (t 1/2 ) of d-MPH is markedly longer than that of l-MPH. 22 The presystemic metabolism and clearance of d,l-MPH is an enantioselective process resulting in markedly higher plasma concentrations of d-MPH relative to l-MPH.…”
mentioning
confidence: 99%